Whole-plant corn, forage sorghum, and grain sorghum silages for growing cattle - Dalke, B.S.; Sonon, R.N.; Gramlich, S.M.; Bolsen, K.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Agronomic and cattle performance traits were measured for eight silages produced in 1991. The silages were: irrigated Pioneer 3377 corn; dryland (early-planted) DeKalb 535 corn; irrigated and dryland DeKalb DK 42Y grain sorghum; and dryland forage sorghums Cargill 200F, Pioneer 947, Northrup King (NK) 300, and Funk's 102F. The irrigated corn and NK 300 and Funk's 102F forage sorghums had the highest whole-plant dry matter (DM) yields per acre; early-planted corn had the lowest yield. The dryland grain sorghum had the highest grain yield and the early-planted corn, the lowest. Average daily gains (ADG) were excellent for steers fed each of the eight silage rations and reflected the relatively high grain contents of the silages and the high DM intakes (2.37 to 2.81% of body wt). As expected, the irrigated corn silage produced the fastest and most efficient gain; the late-maturing, Funk's 102F forage sorghum produced the slowest and least efficient gain.
Keywords: Beef; Silage; Corn; Forage sorghum; Grain sorghum